2018
DOI: 10.1002/pssa.201800429
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Hot Spot Temperature Simulation for c‐Si Photovoltaic Modules

Abstract: A two‐step method to simulate the spatially resolved temperature of a partially shaded cell in a crystalline silicon photovoltaic (PV) module is presented and tested. First, an efficient module electronic simulation tool computes the operating conditions of a module's constituent cells. Second, a two‐dimensional finite‐element analysis simulation, utilizing forward‐, and revers‐bias electroluminescence measurements, is performed to spatially resolved cell temperature. With an outdoor experiment, un‐encapsulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…In our previous work, we demonstrated how a commercial mono c-Si shingled module could develop peak temperatures as high as 145 C under partial shading conditions. 10 While previous works report high hotspot temperatures (>130 C) due to point defects that become localized concentrations of current, 2,11,12 our study showed comparable temperatures could be reached even without said defects; it is possible to reach such temperatures through uniformly distributed heating alone. Furthermore, secondary heating of unshaded cells was also observed in strings parallel to the shaded string, adding to the risks of hotspots and degradation.…”
Section: Introductioncontrasting
confidence: 53%
“…In our previous work, we demonstrated how a commercial mono c-Si shingled module could develop peak temperatures as high as 145 C under partial shading conditions. 10 While previous works report high hotspot temperatures (>130 C) due to point defects that become localized concentrations of current, 2,11,12 our study showed comparable temperatures could be reached even without said defects; it is possible to reach such temperatures through uniformly distributed heating alone. Furthermore, secondary heating of unshaded cells was also observed in strings parallel to the shaded string, adding to the risks of hotspots and degradation.…”
Section: Introductioncontrasting
confidence: 53%
“…Especially multi crystalline silicon (mc-Si) solar cells are prone to hot spots due to the local junction breakdown [11,12]. Hence, many studies have investigated this effect for mc-Si solar cells and developed electrical and thermal models to simulate the effects of inhomogeneous illumination on PV panel [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%